1997
DOI: 10.1677/joe.0.1520345
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and oxytocin levels during normal pregnancy: effects of chronic dietary sodium restriction

Abstract: Neurohypophysial hormones are thought to be involved in alterations in fluid balance during pregnancy and delivery. In the course of normal pregnancy intravascular volume is increased whereas sodium restriction is thought to reduce plasma volume and cardiac output. In the present study, we measured the effect of long-term severe sodium restriction on vasopressin (AVP) and oxytocin (OT) levels during normal pregnancy and after delivery.Fifty-nine healthy nulliparous women were randomized either for a low sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…26 Fasting levels of insulin are raised in the 3rd trimester of pregnancy in women who later develop hypertension, 27 and hyperinsulinemia produces sympathetic activation. 28 Reduction in vasopressin levels has also been reported in pregnacy, 29 and infusion of this hormone has been shown to decrease MSNA. 30 More recently it has been shown that MSNA is greater in young women during the midluteal compared with early follicular phase of the menstrual cycle, when estradiol and progesterone are elevated, 31 and in pregnancy these hormones are additionally elevated.…”
Section: Discussionmentioning
confidence: 91%
“…26 Fasting levels of insulin are raised in the 3rd trimester of pregnancy in women who later develop hypertension, 27 and hyperinsulinemia produces sympathetic activation. 28 Reduction in vasopressin levels has also been reported in pregnacy, 29 and infusion of this hormone has been shown to decrease MSNA. 30 More recently it has been shown that MSNA is greater in young women during the midluteal compared with early follicular phase of the menstrual cycle, when estradiol and progesterone are elevated, 31 and in pregnancy these hormones are additionally elevated.…”
Section: Discussionmentioning
confidence: 91%
“…Thus it would seem that in the context of a securely-attached female with low separation anxiety, oxytocin release, a key factor shown by past research in regulating the mother’s response to stress, assists in promoting positive affiliation with supportive attachment figures and in shaping optimal bonding with her infant [37]. While it is possible that breastfeeding is associated with an increase in oxytocin levels, previous research has indicated that there are no differences in oxytocin between breast-feeding and non-breast-feeding mothers when samples are not taken during actual breast-feeding [38] since oxytocin production is not pulsatile when mothers are not nursing [39].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sodium restriction during pregnancy has raised concerns that it would limit the volume expansion characteristic of normal pregnancy. Sodium restriction implemented after the first 12 weeks of pregnancy does not appear to be harmful in normotensive women, 52,53 but there are no data to support that sodium restriction limits the occurrence of preeclampsia. 54 ACOG recommends against the use of very low salt diets (<100 mEq/dy) to manage chronic hypertension in pregnancy.…”
Section: Lifestyle Modification For Blood Pressure Control During Prementioning
confidence: 99%